Phenomenology of Reference in Male Seduction: “Pragmatic Love” by Alia Mamdouh as a Model - Abbas, Ass.Prof Dr. Mohammed Jasim Mohammed (Thi Qar Arts Journal, 2024)
The research frames its critical approaches on two axes. The first deals with the "phenomenological concept," relying on its principal propositions, along with a section on procedural intersection based on philosophical comments that literary theorists have made consistent with the specificity of the literary work. This makes "the coupling of phenomenology with the conditions of literature" a key to the method's validity before concluding with the observation of "probability and the signs of appearance" and "reference and the ways of introspection." The other axis explored the references to male seduction in the novel "Pragmatic Love" by the novelist "Alia Mamdouh." It observed the manifestations of reference in the seductive models it contained, where the male character "Bahr" exercised persuasive skill to attract the female "Rawiya," through studies of "reference through the logic of seduction," "reference through imaginative seduction," "reference through the culture of seduction," and "reference through physical seduction." The research concluded with results, the most important of which was that Gadamer and Ricoeur contributed to the crystallization of a phenomenology reconciled with literature. Moreover, the studied novel broke the conventions of seduction and made its areas of effectiveness carry a referential energy that reorders the structure and meaning to achieve implicit plots, the evidence of which the reader creates.